Analysis of Factors Influencing Patient Compliance to Treatment at Hospital X - Turnawan, Ikhsan; Susanti, Ai Susi (International Journal of Psychology and Health Science, 2025)
Patient adherence to treatment is an essential component in achieving successful therapy, especially in the management of chronic diseases that require long-term treatment and active patient involvement. Non-adherence can lead to therapy failure, increased complications, higher health care costs, and decreased quality of life. This study aims to analyze factors that influence patient adherence to treatment at Hospital X using a descriptive quantitative approach. The study sample consisted of 100 outpatients selected purposively and analyzed using cross-tabulation and chi-square statistical tests. The results of this study indicate that there are still respondents who are not compliant with treatment. Variables that show a significant relationship to compliance are education level (p = 0.034) and family support (p = 0.002). In contrast, gender (p = 0.859) and age (p = 0.640) do not have a significant relationship. These findings underline the importance of education-based interventions that are tailored to the patient's educational background, as well as active family involvement as an integral part of the care process. This study recommends a more holistic service approach, which not only emphasizes clinical aspects, but also considers social, psychological, and cultural factors of patients as important determinants of compliance behavior.